The genetic diversity of ayam ketawa (Gallus gallus domesticus, Linneaus, 1758) in Bangkalan District, Madura Island, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Abinawanto, Zulistiana T, Lestari R, Dwiranti A, Bowolaksono A. 2021. The genetic diversity of ayam ketawa (Gallus gallus domesticus, Linneaus, 1758) in Bangkalan District, Madura Island, Indonesia. Biodiversitas 22: 3145-3155. Ayam Ketawa, a variation of Gallus gallus domesticus Gallus gallus domesticus, comes from  Sidendreng-Rappang (Sidrap) District, South Sulawesi, Indonesia. Apart from Sidrap, ayam ketawa farms are also found in Bangkalan District, on the island of Madura, Indonesia. Ayam ketawa from Bangkalan District often wins national level contests. Therefore, the research was carried out with the aim of knowing the genetic diversity of ayam ketawa in Kamal Subdistrict, Socah Subdistrict, and Burneh Subdistrict, based on bioacoustic, morphometric, and barcoding DNA analysis. The studied ayam ketawa consists of dangdut and slow types. The longest duration (6.00 ± 3.0) seconds was shown by ayam ketawa from Kamal Subdistrict, while the highest number of syllables (7.20 ± 5.80) came from Socah Subdistrict. The results of the Mann-Whitney test showed that eight morphological characters were significantly different (P